UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN GEOGRAFI MELALUI MODEL PEMBELAJARAN BERBASIS PROJECT PADA SISWA KELAS X.1 SMA N 1 IV KOTO - arnimutia arnimutia (JURNAL MANAJEMEN PENDIDIKAN, 2017)
AbstractBased on the results of student learning X.1SMA N 1 Class IV Koto in geography subjects found that results for students in the subjects of geography is still very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about the efforts to improve student learning outcomes in subjects Geography analyze the dynamics and trends of the lithosphere and pedosphere changes and their impact on life on earth through Project Based Learning Model in Class X.1 SMA N 1 IV Koto Agam ,This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of 24 students Grades X.1 SMA N 1 IV Koto. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the Project Based Learning model can improve student learning outcomes in subjects Geography analyze the dynamics and trends of the lithosphere and pedosphere changes and their impact on life on earth in SMA N 1 IV Koto. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 50.67 (Enough) increased to 84.50 (Good) with an increase of 33.83%.Keywords: Learning Outcomes, Geography, Project Based Learning model